Word Recognition and Word Prediction in Preschoolers With (a Suspicion of) a Developmental Language Disorder: Evidence From Eye Tracking. - Alphen, Petra van; Brouwer, Susanne; Davids, Nina; Dijkstra, Emma; Fikkert, Paula (Journal of Speech, Language & Hearing Research, 2021)
Purpose: This study compares online word recognition and prediction in preschoolers with (a suspicion of) a developmental language disorder (DLD) and typically developing (TD) controls. Furthermore, it investigates correlations between these measures and the link between online and off-line language scores in the DLD group. Method: Using the visual world paradigm, Dutch children ages 3;6 (years;months) with (a suspicion of) DLD (n = 51) and TD peers (n = 31) listened to utterances such as, “Kijk, een hoed!” (Look, a hat!) in a word recognition task, and sentences such as, “Hé, hij leest gewoon een boek” (literal translation: Hey, he reads just a book) in a word prediction task, while watching a target and distractor picture. Results: Both groups demonstrated a significant word recognition effect that looked similar directly after target onset. However, the DLD group looked longer at the target than the TD group and shifted slower from the distractor to target pictures. Within the DLD group, word recognition was linked to off-line expressive language scores. For word prediction, the DLD group showed a smaller effect and slower shifts from verb onset compared to the TD group. Interestingly, within the DLD group, prediction behavior varied considerably, and was linked to receptive and expressive language scores. Finally, slower shifts in word recognition were related to smaller prediction effects. Conclusions: While the groups’ word recognition abilities looked similar, and only differed in processing speed and dwell time, the DLD group showed atypical verb-based prediction behavior. This may be due to limitations in their processing capacity and/or their linguistic knowledge, in particular of verb argument structure.